Protective efficacy of a 62-kilodalton antigen, HIS-62, from the cell wall and cell membrane of Histoplasma capsulatum yeast cells. - Gomez, F J (1991)
We reported previously that a detergent extract of the cell wall and cell membrane of Histoplasma capsulatum yeast cells contains antigens recognized by T cells. In T-cell immunoblot analysis, a region encompassing 62 kDa was stimulatory for an H. capsulatum-reactive T-cell line and T-cell clones derived from C57BL/6 mice. In this study, we isolated a 62-kDa band, termed HIS-62, from electrophoresed cell wall and cell membrane of H. capsulatum yeast cells and examined its antigenicity and immunogenicity. C57BL/6, BALB/c, and CBA/J mice that were immunized with viable H. capsulatum yeast cells mounted a delayed-type hypersensitivity response to HIS-62 that was stronger than that of normal controls. Spleen cells from each strain of mouse immunized with viable yeast cells proliferated vigorously in response to HIS-62; conversely, splenocytes from control animals did not recognize this antigen. A T-cell line and 5 of 5 T-cell clones from C57BL/6 mice, 10 of 15 BALB/c T-cell hybridomas, and 8 of 12 CBA/J T-cell hybridomas recognized HIS-62. A cutaneous delayed-type hypersensitivity response to the antigen was apparent in each strain of mouse that was injected with 80 micrograms of HIS-62 mixed with Freund adjuvant. In addition, spleen cells from HIS-62-immunized mice proliferated in vitro in response to this antigen. Vaccination of each strain of mouse with 80 micrograms of HIS-62 conferred protection against a lethal intravenous challenge with H. capsulatum yeast cells. Thus, HIS-62 appears to be an important target of the cellular immune response to H. capsulatum and induces a protective immune response in mice.